2016
DOI: 10.1186/s12862-016-0821-y
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of genital complexity and mating rates in sexually size dimorphic spiders

Abstract: BackgroundGenital diversity may arise through sexual conflict over polyandry, where male genital features function to manipulate female mating frequency against her interest. Correlated genital evolution across animal groups is consistent with this view, but a link between genital complexity and mating rates remains to be established. In sexually size dimorphic spiders, golden orbweaving spiders (Nephilidae) males mutilate their genitals to form genital plugs, but these plugs do not always prevent female polya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…Stockley (2002), for example, found that in primates, relatively high penile spinosity was associated with lower potential reproductive rates in females and interpreted this in terms of internal damage caused to the female by the spines. Kuntner et al (2016) similarly found that in nephilid spiders, the male's genitalia were more complex in polyandrous species than in monandrous species. Titillators in some bushcrickets have spines (see Figure 1) that contact the soft, un-sclerotised lining of the female's bursa copulatrix (Wulff et al 2015(Wulff et al , 2017.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Stockley (2002), for example, found that in primates, relatively high penile spinosity was associated with lower potential reproductive rates in females and interpreted this in terms of internal damage caused to the female by the spines. Kuntner et al (2016) similarly found that in nephilid spiders, the male's genitalia were more complex in polyandrous species than in monandrous species. Titillators in some bushcrickets have spines (see Figure 1) that contact the soft, un-sclerotised lining of the female's bursa copulatrix (Wulff et al 2015(Wulff et al , 2017.…”
Section: Discussionmentioning
confidence: 83%
“…Comparative evidence indicates that the presence of titillators is associated with longer copulation durations (prior to spermatophore transfer) in bushcrickets (Vahed et al 2011), but the relationship between titillator complexity and polyandry has not previously been examined. In fact, we are not aware of any previous studies that have tested for a relationship across species between direct measures of the degree of polyandry and genital complexity in any animal taxon (for studies that have used in-direct measures of the degree of polyandry or used a binary "monandrous versus polyandrous" classification, see Ramm 2007;Arnqvist 1998;Rowe and Arnqvist 2012;Orr and Brennan 2016;Kuntner et al 2016). Bushcrickets are one of the few animal groups in which data on the lifetime degree of polyandry are available for a range of species (Vahed 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…) populations, as well as the extreme diversification in genitals observed across closely related species (e.g., Kuntner et al. ). Finally, theory predicts that correlational selection will generate a genetic correlation between the two traits by creating linkage disequilibrium (Lande ) or by favoring pleiotropic mutations (Lande ), although these mechanisms are not strictly required if correlational selection is strong and persistent (Sinervo and Svensson ).…”
Section: Discussionmentioning
confidence: 99%
“…As originally proposed by Darwin (1871), two mechanisms of sexual selection, intersexual mate choice and intrasexual competition, now known as intersexual and intrasexual selection, are responsible for the evolution of numerous secondary sexual traits (Darwin, 1871; Andersson, 1994; Edward & Chapman, 2011; Miller & Svensson, 2014; Kuntner et al ., 2016; Buzatto et al ., 2017). In mate choice, females or males actively choose higher‐quality partners (Andersson, 1994; Boughman, 2007; Punzalan et al ., 2008; Omkar & Afaq, 2013; Ortiz‐Jiménez & del Castillo, 2015; Veselinovic et al ., 2017; Goubault & Burlaud, 2018).…”
Section: Introductionmentioning
confidence: 99%